Safe and Reliable Switching of Reactive Capacitor Banks in Sweden’s Industrial Sector - Arnhög Sleman, Maja; Lindström, Patrik (My University, 2025)
Abstract The main scope of this project aims to evaluate methods of limiting inrush current when connecting capacitor banks to a 12.1 kV grid in an industrial environment. Traditionally, Swedish industries have connected large capacitor banks in parallel to the load for reactive power compensation, using asynchronous switching methods. However, the need of reactive power compensation is changing, due to an increase of power electronics and drive systems, requiring lesser amount of reactive power compensation but greater need of filtering. Establishing guiding parameters from accepted international standard IEC 61000-2-4 to measure the performance and behavior of different methods, was a major part of the evaluation method. Depending on the amount of reactive power (Q) compensation and harmonic filtering needed, this report suggests different solutions for different use cases. For low frequent switching rates: A pre-insertion resistor is suitable for cases with major need of Q-compensation together with a small inrush reactor. A de-tuned filter is suitable when low amounts of Q-compensation is needed, but instead the need of filtering is large. Further, a TSC is applicable for any scenario of the above, with the additional feature of being able to switch asynchronously and more frequent than the regular synchronous/asynchronous breakers. Finally, a theoretical example of a strategy using variable resistance is also evaluated, with impressive results in limiting inrush currents during switching. Even though this is not yet typically deployed for 12.1 kV voltage levels, this is by far the most effective strategy evaluated.
Keywords: Keywords: inrush current, asynchronous switching, synchronous switching, drivesystems, capacitor-bank, inrush reactor, de-tuned filter, TSC, pre-insertion resistor.